Mongolian Freshwater Ecosystems Under Climate Change and Anthropogenic Pressure: A Case Study of Ugii Lake - Itgelt Navaandorj; Erdenetsetseg Tsogtbayar; Solongo Tsogtbaatar; Gerelt-Od Dashdondog; Mandakh Nyamtseren; Kikuko Shoyama (Land)
This study investigates the hydrological, ecological, and socio-economic responses of Ugii Lake—a freshwater body in semi-arid Central Mongolia—to climate variability and anthropogenic pressures. Seasonal field surveys conducted during the spring, summer, and fall of 2023–2024 revealed notable spatial and temporal variation in water quality, with pH ranging from 7.54 to 8.87, EC from 316 to 645 µS/cm, and turbidity between 0.36 and 5.76 NTU. Total dissolved solids (TDS) values and ionic compositions indicated increased salinization in some zones, particularly those exposed to high evaporation and shoreline disturbance. Heavy metal analysis identified elevated levels of aluminum, manganese, and zinc at several sampling points; however, concentrations generally remained within national environmental standards. Vegetation surveys showed that disturbed areas—especially those affected by grazing and tourism—exhibited reduced native plant diversity and dominance of invasive species. Socio-economic interviews with local herders and stakeholders indicated that 67.3% of households experienced declining livestock productivity, and 37.1% reported increased allergies or respiratory symptoms linked to deteriorating environmental conditions. Despite some ongoing conservation efforts, respondents expressed dissatisfaction with enforcement and impact. These findings highlight the need for community-driven, integrated lake management strategies that address environmental degradation, climate adaptation, and rural livelihood security.